Optimalisasi Pemasaran Digital pada Lembaga KB Dinar Nasyi’ah Tanggul Kabupaten Jember - Nur Afni Rachman; Peni Arianita Wardani; Muhamad Farhan; Muksin Muksin; Vemas Aditia (Lembaga Pengembangan Kinerja Dosen, 2024)
The demands of the industrial revolution 5.0, especially in the field of education, require detailed information related to school services that can be accessed by parents and prospective students regardless of location and at any time, in addition to promotions using flyers and banners as in traditional marketing. Unfortunately, not many educational institutions, especially Early Childhood Education Institutions (PAUD), use digital marketing or promotion optimally due to limited knowledge. In fact, digital marketing is more affordable than trying traditional marketing. DINAR Nasyi'ah Tanggul Playgroup as a partner is one of the PAUD institutions that uses traditional marketing and has not maximized digital marketing in providing information about PAUD. This is not only due to cost constraints but also the digital capabilities of PAUD managers who still need to learn. In addition, PAUD managers are also constrained by the lack of marketing management capabilities. The methods used to overcome partner problems include the needs analysis stage, the activity preparation stage, initial assessment, promotion management training, creating digital and non-digital marketing/promotion media, registering PAUD locations on Google Maps, optimizing PAUD social media, and evaluation. The results of this service show an increase in marketing management knowledge, as well as partner digital marketing capabilities. In addition, there is the availability of digital and non-digital promotional media which are assistance products from the community service team.